PROFIL PENGRAJIN ANYAMAN TIKAR PANDAN DI KORONG MUARO NAGARI KURAI TAJI KECAMATAN NAN SABARIS KABUPATEN PADANG PARIAMAN - Fitriani, Riri; Rianto, Slamet; U, Iswandi (Pendidikan Geografi, 2013)
The craft production of âTikar Pandanâ at the village of Muaro, Kurai Taji Village, Subdistrict ofÂ  Nan Sabaris of Padang Pariaman Regency was one of society economic activity traditionally. This craft have economic elements which related to cultural aspect and arts, because its existence as cultural heritage and the proud of the vicinity of people who lived there. The business have done for long time at the village of Muaro, Kurai Taji Village, Subdistrict ofÂ  Nan Sabaris of Padang Pariaman Regency, especially to fulfill their essential needs, and even executed from generation to generation.Â  This research aims to know the data and information about The Handy Crafter Profile of âTikar Pandanâ at the village of Muaro, Kurai Taji Village, District ofÂ  Nan Sabaris of Padang Pariaman Regency, motivation, raw material,Â  production equipment, income, marketing, the crafter of Tikar Pandanâ at the village of Muaro, Kurai Taji Village, Subdistrict ofÂ  Nan Sabaris. The type of this research was qualitative by using interview method, observation and filed research. And then data was collected by guiding interview, observation and documentation. After the data of research was collected, and then the data to be analyzed by using descriptive words.The result of field research showed that a) motivation of crafter âTikar Pandanâ were : improve their household income and protect the culture, b) raw material was used by crafter was daun pandan berduri (pandanase torn leaf), c) the equipmentÂ  was used by crafter such as ladiang (sword), saga made from zinc with the length size between 10-15 cm and panyrauik (grind) made from bamboo with the length size between 15-18 cm with width about 3-4 cm. the grind was used to soften the pandanase leaf. d) by working as a crafter, they get income in the range from Rp. 28.000,- toÂ  Rp. 50.000,- weekly and other business like collection of chili with averageÂ  income Rp. 175.000,- and sewing/revised the dress give income about Rp. 50.000,-. e) The way of marketing their craft of Tikar Pandan was executed by directly marketing to costumer by agent to the market